ANALYSIS OF INTEREST IN SAVING IN SHARIA BANK AMONG FEBI STUDENTS OF UIN SMH BANTEN - M, Shiffa Aida; A, Athiyya Rizky; Azahra, Luvita; Saraswati, Henny; Hidayat, Wahyu (Institut Agama Islam Negeri Parepare, 2023)
This study aims to find out the students of UIN SMH Banten in Islamic Banks. Questionnaires were distributed to 32 FEBI students at UIN SMH Banten, Serang City. The collected data were analyzed using descriptive and inferential statistics. Based on the data obtained, it is known that the variables of bank reputation and beliefs influence the interest in saving for UIN SMH Banten students in Islamic banks. The purpose of this study is to analyze the interest of FEBI students at UIN SMH Banten in saving at Islamic banks. This research is quantitative descriptive research using primary data. The variables used in this study consist of bank reputation and trust as independent variables and interest in saving students as the dependent variable. The data collection method uses by providing questionnaires. The method used in this research is descriptive analysis.The results of the study show that the difference between men and interest in savings in Islamic banks is significantly different. Keywords: Analysis, Interest in Saving, Islamic Banks, FEBI Students